2022
DOI: 10.1029/2021gl097591
|View full text |Cite
|
Sign up to set email alerts
|

Stress Heterogeneity and the Onset of Faulting Along Geometrically Irregular Faults

Abstract: Faulting in rocks occurs when accumulated elastic stress is released along weak discontinuities. The event characteristics depend on the loading conditions, the mechanical properties of the rocks, and the geometry of the fault. Quantifying the effect of geometrical irregularities on stress accumulation and material yielding is therefore fundamental for evaluating fault stability at a wide range of scales and in various tectonic and geoengineering settings. For example, laboratory experiments demonstrate that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The mathematical similarity of the stress field allows for "translating" the geometrical interface irregularity (i.e., two-body) into damage heterogeneity (i.e., three-body). It can be shown (Morad et al, 2022;Sagy & Lyakhovsky, 2019) that the solution, as demonstrated here for the simple sinusoidal damage heterogeneity (Equation 6), is valid for a stochastic damage distribution (Figure 2b) and for stress around a homogenous damage layer with thickness heterogeneity (Figure 2c). The thickening of the damage zone leads to the same stress variations as the reduction of the shear modulus.…”
Section: Static Stress Distribution Around Heterogenic Layermentioning
confidence: 67%
See 4 more Smart Citations
“…The mathematical similarity of the stress field allows for "translating" the geometrical interface irregularity (i.e., two-body) into damage heterogeneity (i.e., three-body). It can be shown (Morad et al, 2022;Sagy & Lyakhovsky, 2019) that the solution, as demonstrated here for the simple sinusoidal damage heterogeneity (Equation 6), is valid for a stochastic damage distribution (Figure 2b) and for stress around a homogenous damage layer with thickness heterogeneity (Figure 2c). The thickening of the damage zone leads to the same stress variations as the reduction of the shear modulus.…”
Section: Static Stress Distribution Around Heterogenic Layermentioning
confidence: 67%
“…Following previous works (F. M. Chester & Chester, 2000;Morad et al, 2022), the perturbation of the shear stress component, 𝐴𝐴 𝐴𝐴 (1) 𝑥𝑥𝑥𝑥 , for the static stress distribution near such interface, is proportional to the remote stress, 𝐴𝐴 𝐴𝐴 (0) 𝑥𝑥𝑥𝑥 , and decays exponentially with the distance, z, from the interface:…”
Section: Static Stress Distribution Around Heterogenic Layermentioning
confidence: 71%
See 3 more Smart Citations